Water Status,Vegetative Growth and Yield Responses of Vitis vinifera L. cvs. Sauvignon blanc and Chenin blanc to Timing of Irrigation during Berry Ripening in the Coastal Region of South Africa - Myburgh, P.A. (South African Journal of Enology and Viticulture, 2017)
The effects of additional irrigation during berry ripening on water relations, growth and yield in Sauvignon blanc and Chenin blanc grapevines were investigated. In all treatments the grapevines were irrigated when berries reached pea size in December. One treatment received no further irrigation until after harvest. All of the remaining treatments received a second irrigation at véraison. Except for a single treatment, which was not irrigated during ripening, these treatments received a third irrigation at either 14, 21, 28 or 31 days after véraison. The six treatments were applied in a field trial carried out in the Stellenbosch district of the coastal winegrowing region of South Africa over consecutive seasons, between 1990 and 1993. Irrigation at pea size berries and at pea size berries plus véraison increased leaf water potential, but did not affect vegetative growth and yield in either cultivar. Relative to a single application at pea size berries, irrigation at pea size, at véraison and during ripening increased berry size in both cultivars, though not consistently, over the three seasons. However, this result must be viewed in terms of the fact that qualitative assessments of root development and distribution have revealed that effective soil preparation contributes to well-developed root systems. Results confirmed that these root systems could sustain vegetative growth and yield where a single irrigation was applied at pea size berries compared with additional irrigations applied at véraison and during ripening. Irrigation applied at, and after, véraison resulted in yield losses of both cultivars when rainfall favoured Botrytis cinerea infection.